Optical member, optical device, imaging device, and method for manufacturing optical member
Patent Information
- Application Number
- JP2020189502
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-11-13
AI Technical Summary
【0008】 本発明によれば、多孔質層の吸湿が抑制された、部材および部材の製造方法を実現することができる。
Smart Images

Figure 0007638672000004 
Figure 0007638672000005 
Figure 0007638672000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical member having excellent antifogging properties and optical performance, and a method for producing the optical member. [Background technology]
[0002] When the surface of a transparent substrate such as glass or plastic is cooled below the dew point, minute water droplets adhere to the substrate surface, scattering transmitted light and impairing transparency, resulting in a so-called "cloudy" state. Therefore, transparent members in particular are often required to have anti-fog properties in addition to optical properties such as anti-reflection.
[0003] Patent Document 1 discloses an optical component that achieves anti-reflection and anti-fogging properties by providing a porous structure in which metal oxide particles are bound by a binder on a substrate and by adsorbing moisture in the air into the porous structure. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-105846 A Summary of the Invention [Problem to be solved by the invention]
[0005] When moisture is absorbed into the voids of the porous structure, the air in the voids is replaced with water, causing an increase in the refractive index. Therefore, when the member of Patent Document 1 is exposed to an environment where anti-fogging performance is required and the porous structure absorbs moisture, the refractive index increases. This causes a change from the optically designed state when no moisture is absorbed, resulting in a significant decrease in anti-reflection performance. [Means for solving the problem]
[0006] The present invention aims to solve the above problems, Porous layer Sucking Humidity Suppressed , DepartmentThe present invention aims to provide a method for manufacturing materials and components.
[0007] The member of the present invention is a member comprising a porous layer on a substrate, the porous layer having, in order from the substrate side, a first region, a second region, and a third region, the first region containing first particles, the third region containing second particles having a shape different from that of the first particles, and the second region containing the first particles and the second particles, and the average porosity of the second region is greater than the average porosity of the first region and less than the average porosity of the third region. Effect of the Invention
[0008] According to the present invention, Porous layer Sucking Humidity Suppressed , Department It is possible to realize a method for manufacturing materials and components. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1(a) is a schematic diagram showing one embodiment of an optical member according to the present invention, and FIG. 1(b) is an enlarged view of a porous layer. [Diagram 2] FIG. 1(a) shows a member in which only a porous layer is formed on a substrate, and FIG. 1(b) shows a member in which a vapor-deposited film layer is formed between the porous layer and the substrate. [Diagram 3] FIG. 1 is a schematic diagram of an embodiment of an optical member according to the present invention, which has a front-surface antireflection layer. [Figure 4] FIG. 1 is a schematic diagram of an embodiment of an optical member according to the present invention, the member having an underlying anti-reflection layer. [Diagram 5] FIG. 1 is a schematic diagram of an embodiment of an optical member according to the present invention, which has a hydrophilic polymer layer. [Figure 6] 1 is a schematic diagram showing an example of the configuration of an imaging device according to the present invention; [Figure 7] FIG. 2 is a diagram showing the reflectance characteristics before and after water absorption in Example 1. [Figure 8] FIG. 1 is a diagram showing the reflectance characteristics before and after water absorption in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present invention will be described, but unless otherwise specified, the present invention is not limited to these embodiments.
[0011] [Optical components] FIG. 1(a) is a schematic diagram showing one embodiment of the member of the present invention.
[0012] The member 100 of the present invention has a porous layer 20 including, in order from the substrate side, a first region 21, a second region 22, and a third region 23 on a substrate 10, and has antifogging properties and antireflection layer properties. In the figure, a configuration having the porous layer 20 on one side of the substrate 10 is shown, but the porous layer 20 may be provided on both sides of the substrate 10 depending on the application.
[0013] By appropriately selecting the substrate 10, the member 100 of the present invention can be used for a wide range of applications, such as window glass, mirrors, lenses, transparent films, etc. It is particularly suitable for applications such as optical lenses for imaging and projection systems, optical mirrors, optical filters, eyepieces, flat covers and dome covers for outdoor cameras and surveillance cameras, face shields and mouth shields.
[0014] (base material) The material of the substrate 10 may be glass, resin, etc. The shape of the substrate 10 is not limited, and may be flat, curved, concave, convex, or film-like.
[0015] The glass may be an inorganic glass containing zirconium oxide, titanium oxide, tantalum oxide, niobium oxide, hafnium oxide, lanthanum oxide, gadolinium oxide, silicon oxide, calcium oxide, barium oxide, sodium oxide, potassium oxide, boron oxide, aluminum oxide, etc. The glass substrate may be shaped by grinding and polishing, molding, float forming, or the like.
[0016] The resin may be polyethylene terephthalate, polyethylene naphthalate, triacetyl cellulose, acrylic resin, polycarbonate, cycloolefin polymer, polyvinyl alcohol, or the like.
[0017] For the purpose of improving the strength and flatness of the substrate 10, and improving the adhesion of a film in contact with the substrate 10, the surface of the substrate 10 may be cleaned or polished, or a functional layer such as an adhesive layer or a hard coat layer may be provided.
[0018] (Porous layer) Fig. 1(b) shows an enlarged view of the porous layer 20. The first region includes first particles 24, the third region includes second particles 25 that are different in shape from the first particles, and the second region includes both the first particles 24 and the second particles 25. "Different shapes" here also includes similar shapes that simply differ in size. Fig. 1(b) shows a case where the first particles 24 are spherical particles and the second particles 25 are chain-like particles.
[0019] Voids are formed between the particles contained in the porous layer 20, and the particles are three-dimensionally connected to each other and connected to the outside air. With this porous structure, when the humidity of the external environment of the member increases, the moisture contained in the air that has infiltrated into the voids of the porous layer 20 is condensed and adsorbed, thereby exhibiting anti-fogging properties. In addition, since the voids contained in the porous layer 20 are connected to each other, it is possible to adsorb moisture by utilizing all the voids contained in the layer, and high anti-fogging performance can be exhibited.
[0020] In the porous layer 20 of the member according to the present invention, the average porosity of the second region 22 is larger than that of the first region 21 and smaller than that of the third region 23. In the porous layer 20, the third region 23 has the largest average porosity and mainly plays a role of adsorbing moisture. Therefore, if the porous layer 20 is required to have only anti-fogging performance, it is sufficient to have only the third region, but if anti-reflection performance is required in addition to anti-fogging performance, the third region alone is insufficient. The reason for this is explained below.
[0021] 2(a), consider the case where a porous layer 220 with a high porosity for anti-fogging purposes is formed directly on a substrate 10. The refractive index of the substrate 10 made of glass or resin is about 1.5, whereas the refractive index of the porous layer 220 provided for anti-fogging purposes is about 1.2 to 1.3. When the difference in refractive index is large like this, light reflection R1 occurs at the interface between the substrate 10 and the porous layer 220.
[0022] In order to reduce the light reflection occurring at the interface between the substrate 10 and the porous layer 220, a configuration shown in FIG. 2(b) is considered in which a layer 221 having a refractive index intermediate between the refractive index of the porous layer 220 and the refractive index of the substrate 10 is provided between the porous layer 220 and the substrate 10. The refractive index difference between the porous layer 220 and the layer 221 is set to be approximately the same as the refractive index difference between the substrate 10 and the porous layer 220, and the film thickness of the layer 221 is set to an integer multiple of λ / 4 of the wavelength λ to be reduced. With this configuration, it is possible to reduce the reflected light by interference between the reflected light R1 at the interface between the layer 221 and the substrate 10 and the reflected light R2 at the interface between the porous layer 220 and the layer 221.
[0023] However, the configuration of Fig. 2(b) has the following problem. When the optical member is exposed to a high-humidity environment and the porous layer 220 adsorbs moisture (absorbs moisture), the air in the pores is replaced with water, and the refractive index of the porous layer 220 increases. When the layer 221 is a layer with a low porosity such as a vapor deposition film, the refractive index of the layer 221 hardly changes even when it absorbs moisture, and the refractive index difference between the porous layer 220 and the layer 221 becomes smaller than the refractive index difference between the porous layer 220 and the substrate 10. Then, the balance of the intensities of the reflected light R1 and the reflected light R2 is lost, and the reflected light cannot be sufficiently reduced due to interference.
[0024] Therefore, it was found that if an attempt is made to reduce the difference in refractive index caused by moisture absorption by making layer 221 into porous layer 221' whose porosity is adjusted to be approximately intermediate between the porosity of porous layer 220 and the porosity of substrate 10, and by making porous layer 221' also absorb moisture, a new problem arises.
[0025] When the porous layer 220 is formed on the porous layer 221', a dense region with a small porosity is formed at the interface between the porous layer 221' and the porous layer 220, blocking the movement of moisture. Therefore, the moisture adsorbed in the porous layer 220 cannot move to the porous layer 221' and remains in the porous layer 220. If only the refractive index of the porous layer 220 that adsorbs moisture increases and the refractive index of the porous layer 221' does not change, the balance of the intensity of the reflected light at each interface is lost for the same reason as when the layer 221' is a vapor deposition film, and the reflected light cannot be sufficiently reduced.
[0026] It is believed that the dense region formed at the interface between the porous layer 221' and the porous layer 220 is due to the fact that particles are densely aggregated at the surface of the coating liquid where drying begins first when the coating liquid is dried to form the porous layer 221'. Therefore, in the present invention, as shown in Fig. 1(b), a second region 22 containing first particles 24 and second particles 25 is provided between a first region 21 corresponding to the porous layer 221' and a third region 23 corresponding to the porous layer 220.
[0027] The second region can be formed by applying a coating liquid for forming the first region 21 to the substrate, and applying a coating liquid for forming the third region 23 before the coating liquid dries. The second region 22 contains both the first particles 24 and the second particles 25, and therefore has a porosity intermediate between the porosity of the first region 21 and the porosity of the third region, and it is possible to suppress the formation of a dense region. The second region may be formed by applying a coating liquid for forming the first region 21 to the substrate, applying a coating liquid containing the first particles and the second particles before the coating liquid dries, and applying a coating liquid for forming the third region 23 before the coating liquid dries.
[0028] If there is no dense region between the first region 21 and the third region 23 that prevents the movement of moisture, the moisture adsorbed in the third region 23 moves to the first region 21 via the second region 22. The refractive index of the first region 21 and the second region 22 also increases due to moisture adsorption, similar to that of the third region 23. As a result, even when the porous layer 20 adsorbs moisture, the refractive index difference between the first region 21 and the third region 23 and the refractive index difference between the third region 23 and the substrate 10 become approximately the same, and the intensity of the light reflected at each interface also becomes approximately the same, so that it is possible to maintain the anti-reflection performance.
[0029] From the viewpoint of anti-fogging and anti-reflection, the porosity of the first region is preferably 10% to 30%, and the porosity of the third region is preferably 40% to 60%, where the porosity refers to the ratio of the total area of voids contained in any region in the cross section of the porous layer.
[0030] The porosity can be calculated by the following method. First, the porous layer 20 is sliced in the film thickness direction at an arbitrary position, and an observation image is obtained by a scanning transmission electron microscope (STEM). The acquired image is processed using Image Pro PLUS (manufactured by Media Cybernetics, Inc.) or the like, and the void and non-void parts are binarized to calculate the total area of the voids in each region. Then, the ratio of the area occupied by the voids in each region of the porous layer is calculated to obtain the porosity. The porosity is preferably calculated for a region of 150 nm x 150 nm or more including each region in the cross section of the porous layer 20.
[0031] 1(b) shows a case where the first particles 24 are spherical particles and the second particles 25 are chain-like particles, but the present invention is not limited to this as long as the average porosity of the third region can be made larger than the average porosity of the first region. For example, the first particles 24 and the second particles 25 may both be spherical particles, and the particle diameter of the second particles 25 may be larger than that of the first particles 24. It is preferable to select a shape and particle diameter for the first particles 24 such that fewer voids are formed between the particles than for the second particles 25.
[0032] The first particles 24 and the second particles 25 may be used alone or in combination, and may be appropriately selected from various shapes such as spherical, chain-like, disk-like, elliptical, rod-like, needle-like, and angular. Spherical or chain-like shapes are particularly preferred because they have excellent film-forming properties and can increase the porosity while providing sufficient film hardness. Particles of different shapes may also be used in combination.
[0033] Chain particles are an aggregate of particles in which multiple particles are linked together in a chain (also called a rosary shape) in a straight or curved manner. The shape of the particles that form the chain particles may be such that the individual particles can be clearly observed, or may be fused together and lose their shape, and the chain structure is maintained even when the particles are formed into a film. Therefore, the gaps between the particles can be made larger than when particles of other shapes are used, and a porous layer with a large pore volume can be formed.
[0034] When spherical, discoid, or elliptical particles are used for the first particles 24 or the second particles 25, the average particle diameter is preferably 5 nm or more and 100 nm or less. If the average particle diameter is 5 nm or more, the compressive stress during film formation can be released, so that cracks tend not to occur. If the average particle diameter is 100 nm or less, light scattering due to the particle size is unlikely to occur, and a highly transparent film is likely to be obtained. A more preferable average particle diameter is 10 nm or more and 60 nm or less.
[0035] When chain-like, rod-like, or needle-like particles are used for the first particles 24 or the second particles 25, the average short diameter is preferably 5 nm to 40 nm, and more preferably 8 nm to 30 nm. If the average short diameter is 5 nm to 40 nm, reliability loss and scattering due to the incorporation of moisture and chemicals in the atmosphere are unlikely to occur. The ratio of long diameter / short diameter is preferably 3 to 12, and more preferably 4 to 10. If the ratio of long diameter / short diameter is within this range, it is easy to increase the pore volume, and at the same time, it is easy to suppress light scattering and obtain high transparency.
[0036] Here, the average particle size of the particles is the average Feret's diameter. This average Feret's diameter can be measured by image processing of an image observed by a transmission electron microscope. As an image processing method, a commercially available image processing such as Image Pro PLUS (manufactured by Media Cybernetics) can be used. In a specified image area, the contrast is appropriately adjusted if necessary, and the average Feret's diameter of each particle is measured by particle measurement, and the average value is calculated.
[0037] The first particles 24 and the second particles 25 may each be particles of a single metal oxide mainly composed of silicon oxide or zirconium oxide, or may have some of the elements replaced with other elements such as Al, Ti, Zn, Zr, or B, or may have an organic group bonded thereto. Particles mainly composed of silicon oxide are particularly preferred in that they lower the refractive index of the porous layer 20 and provide excellent chemical stability.
[0038] In order to increase the strength (scratch resistance) of the porous layer 20, it is advisable to bond the particles together. Methods for bonding the particles together include a method of physically bonding the particles using a binder and a method of chemically bonding the particles together by treating the surfaces of the particles. As the binder, either an organic binder or an inorganic binder can be used, but a chemically stable inorganic binder is preferred, and a silicon oxide compound is particularly preferred. A suitable example of a silicon oxide compound is a silicon oxide oligomer obtained by hydrolysis and condensation of a silicate ester.
[0039] The average pore size of the pores contained in the porous layer 20 is preferably 3 nm or more and 50 nm or less, as determined by pore distribution measurement using a nitrogen gas adsorption method. If the average pore size is 3 nm or more, air and moisture can move smoothly through the porous layer 20, making it possible to achieve sufficient anti-fogging performance. If the average pore size is 50 nm or less, there are fewer pores with a pore size exceeding 100 nm that cause light scattering, making it possible to achieve high transparency. A more preferred pore size is 5 nm or more and 20 nm or less.
[0040] The amount of voids contained in the porous layer 20 can be determined as pore volume by nitrogen gas adsorption. The pore volume is preferably 0.1 cm3 / g or more and 1.0 cm3 / g or less. When the pore volume is 0.1 cm3 / g or more, the porous layer 20 can retain a sufficient amount of water to obtain anti-fogging properties. When the pore volume is 1.0 cm3 / g or less, sufficient scratch resistance can be obtained without reducing the hardness of the skeleton. A more preferable pore volume is 0.3 cm3 / g or more and 0.6 cm3 / g or less.
[0041] The third region 23 of the porous layer 20, which is exposed to the external environment, is mainly responsible for adsorbing moisture, and therefore is desired to have voids capable of adsorbing the amount of moisture required for the application. Therefore, the thickness of the third region 23 should be set according to the anti-fogging performance required. The thicker the third region is, the higher the anti-fogging performance becomes, but when the porous layer 30 is made of an inorganic material, if the film thickness is too thick, cracks due to stress will occur, so the thickness is preferably 0.2 μm or more and 2 μm or less. More preferably, it is 0.2 μm or more and 1.5 μm or less.
[0042] The thickness of each of the first region 21 and the second region 22 may be determined according to the optical design. The first region 21 may have a thickness equal to an integer multiple of λ / 4 of the wavelength λ to be reduced, and is preferably set to 50 nm or more and 150 nm or less. Within this range, the reflection of the wavelength λ of visible light can be reduced under interference conditions.
[0043] The physical thickness of each region can be measured from an image obtained by using a scanning transmission electron microscope (STEM) after cutting a thin film on an optical component using an electron beam processing device to expose a cross section of the film.
[0044] (Surface anti-reflection layer) In order to further enhance the anti-reflection effect of the member, it is also preferable to provide a front-surface anti-reflection layer 30 on the porous layer 20 as shown in FIG.
[0045] The front-surface antireflection layer 30 has antireflection performance to suppress reflection at the light-incident / exit interface of the member, and moisture permeability to enable the movement of moisture between the outside and the porous layer 20. The front-surface antireflection layer 30 is a laminate of multiple layers having different refractive indices, and a high refractive index layer, a medium refractive index layer, and a low refractive index layer are appropriately combined according to the optical design. In order to reduce the difference in refractive index between the front-surface antireflection layer 30 and the air and suppress reflection, a low refractive index layer is provided on the outermost surface of the front-surface antireflection layer 30. The front-surface antireflection layer 30 is preferably formed by a vapor deposition method.
[0046] In the present invention, a layer with a refractive index of 1.8 or more is called a high refractive index layer, a layer with a refractive index of 1.4 or more and less than 1.8 is called a medium refractive index layer, and a layer with a refractive index of less than 1.4 is called a low refractive index layer. In the present invention, "transparent" refers to a state in which the transmittance of visible light is 70% or more, and the refractive index is the value (n d ) is shown.
[0047] The low refractive index layer is made of silicon oxide (SiO2, n d =1.46), magnesium fluoride (MgF2, n d =1.38), calcium fluoride (CaF2, n d =1.43) can be used.
[0048] The medium refractive index layer is made of aluminum oxide (Al2O3, n d =1.77), silicon oxide, calcium fluoride, or other inorganic materials can be used.
[0049] The high refractive index layer is made of zirconium oxide (ZrO2, n d =2.13), titanium oxide (TiO2, n d =2.52~2.72), tantalum oxide (Ta2O5, n d =2.17), niobium oxide (Nb2O5, n d =2.32), hafnium oxide (Hf2O5, n d=1.91). The high refractive index layer may contain two types selected from these metal oxides, or may be mixed with another metal oxide to adjust the refractive index.
[0050] The thickness of each layer included in the antireflection layer 30 is preferably 10 nm or more and 200 nm or less. By setting the thickness of each layer within this range, it is possible to reduce the reflection of visible light in a wide wavelength range. In order to suppress the reflectance in a wide wavelength range, the number of stacked layers is preferably 2 or more, and more preferably 3 or more.
[0051] The moisture permeability of the front-surface antireflection layer 30 allows the movement of moisture between the outside and the porous layer 20, and the moisture can be retained in the porous layer 20 or released to the outside air depending on the humidity, thereby repeatedly exerting antifogging properties. In order to give the front-surface antireflection layer 30 moisture permeability, it is preferable to form each layer so as to include pores. A layer having pores within the film can be formed by appropriately adjusting the deposition conditions, such as the introduction pressure of the film-forming gas during deposition, the temperature of the substrate, and the angle of the deposition material flying to the base material. Among them, non-heating deposition and oblique deposition, in which deposition is performed without heating, are preferable.
[0052] The refractive index of a film is determined by its composition and density. For example, the refractive index of magnesium fluoride (MgF2) at true density is n d is 1.38, but if there are 30% vacancies in the film, n d is reduced to 1.27. This is because the vacancies in the film have n d This is because the presence of air, with a refractive index of 1.0, reduces the refractive index of the entire film. Thus, for layers made of the same composition, the denser the film, the higher the refractive index, and the lower the density, the lower the refractive index. By making each layer that makes up the anti-reflection layer a low-density film that contains voids, it is possible to create a film that is easily permeable to moisture.
[0053] In order to prevent the component from fogging, the relative humidity near the surface of the component must be kept below 100%. Since the amount of moisture that the porous layer 20 can hold is limited, it is desirable for the porous layer 20 to start absorbing moisture at a relative humidity as close to 100% as possible.
[0054] Moisture near the surface of the member passes through the front-surface antireflection layer 30 and is adsorbed by the porous layer 20. For example, if the pores of the front-surface antireflection layer 30 are made smaller than those of the porous layer 20, a higher pressure is required for the moisture to move through the front-surface antireflection layer 30 than when it moves through the porous layer 20. In other words, in order for water to diffuse through the front-surface antireflection layer 30 into the porous layer 20, the relative pressure (relative humidity) of the water must be higher than that of the porous layer 20 alone. In this way, by laminating the front-surface antireflection layer 30, which has smaller pores than the porous layer 20, on the porous layer 20, adsorption of water begins at a higher relative humidity than that of the porous layer 20 alone, and the antifogging properties can be further improved.
[0055] Furthermore, if the adsorption of moisture into pores follows the Kelvin law, the humidity at which moisture condenses within the porous layer and begins to adsorb will shift to the higher humidity side as the pores become larger. Since the pores in the front-surface antireflection layer 30 are sufficiently smaller than the pores in the porous layer 20, the front-surface antireflection layer 30 begins to adsorb moisture even in a low-humidity environment where adsorption does not begin in the porous layer 20. For example, if the contact angle of the front-surface antireflection layer 30 to water is 10 degrees and the pore size is 3 nm in diameter, it is expected that moisture adsorption will begin at a relative humidity of 50%.
[0056] In this way, the front-surface antireflection layer 30 starts to adsorb moisture in a lower humidity environment than the porous layer 20, and as the humidity increases, the moisture adsorbed in the front-surface antireflection layer 30 moves to the porous layer 20. As a result, the optical member according to the present invention can exhibit antifogging performance over a wide humidity range.
[0057] The front-surface antireflection layer 30 according to the present invention can retain only a small amount of moisture, so that even if it absorbs moisture, the refractive index does not change significantly. Therefore, it is possible to exhibit antireflection performance even in a high-humidity environment.
[0058] (Base anti-reflective layer) In order to further enhance the anti-reflection effect, it is also preferable to provide an underlying anti-reflection layer 40 between the porous layer 20 and the substrate 10 as shown in Figure 4, thereby reducing the reflection occurring at the interface between the porous layer 20 and the substrate 10.
[0059] The base antireflection layer 40 is preferably a single film having a refractive index between the porous layer 20 and the substrate 10, or a laminated body combining a plurality of layers having different refractive indices, such as a high refractive index layer, a medium refractive index layer, and a low refractive index layer. By utilizing the interference in the base antireflection layer 40, reflection can be reduced not only at the wavelength λ but also in a wider wavelength range. The high refractive index layer, the medium refractive index layer, and the low refractive index layer can each be a film exemplified as the front surface antireflection layer. The base antireflection layer 40 can be formed by a vacuum film formation method such as a deposition method or a sputtering method, or a wet film formation method using a sol-gel liquid or a particle dispersion liquid.
[0060] A configuration including a top antireflection layer 30 in addition to a base antireflection layer 40 is also preferable because it enhances the antireflection effect.
[0061] (Manufacturing method for components) A method for manufacturing the member shown in FIG. 4 will now be described.
[0062] The method for producing the member 100 according to the present invention includes a step of forming a porous layer 20 on a substrate 10 .
[0063] A wet film formation method is used in the process of forming the porous layer 20. When forming the porous layer 20 by the wet method, it is possible to form the layer by forming a coating film on a substrate using a coating liquid containing a metal oxide precursor or metal oxide particles synthesized by a sol-gel method or the like, and drying the coating liquid at 15° C. to 200° C. The coating liquid is not limited to a coating liquid containing a metal oxide precursor or metal oxide particles, and a coating liquid containing polymer particles may also be used.
[0064] The solvent that can be used in the coating liquid for forming the porous layer 20 may be any solvent in which the raw material dissolves uniformly and the reactant does not precipitate. For example, water can be used. In addition, monohydric alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methylpropanol, 1-pentanol, 2-pentanol, cyclopentanol, 2-methylbutanol, 3-methylbutanol, 1-hexanol, 2-hexanol, 3-hexanol, 4-methyl-2-pentanol, 2-methyl-1-pentanol, 2-ethylbutanol, 2,4-dimethyl-3-pentanol, 3-ethylbutanol, 1-heptanol, 2-heptanol, 1-octanol, and 2-octanol can be used. Dihydric or higher alcohols such as ethylene glycol and triethylene glycol can be used. Also usable are ether alcohols such as methoxyethanol, ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, and 1-propoxy-2-propanol, and ethers such as dimethoxyethane, diglyme, tetrahydrofuran, dioxane, diisopropyl ether, dibutyl ether, and cyclopentyl methyl ether. Also usable are esters such as ethyl formate, ethyl acetate, n-butyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, and propylene glycol monomethyl ether acetate. Also usable are various ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone. Also usable are aprotic polar solvents such as N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and ethylene carbonate. Two or more solvents selected from these may be mixed and used.
[0065] For the purpose of improving the wettability between the coating liquid and the coating surface, increasing the thickness uniformity of the layer, and improving the adhesion between the porous layer 20 and the coating surface, additives can be added to the coating liquid for forming the porous layer 20. Examples of additives include surfactants, leveling agents, adhesion promoters, acid catalysts, etc., and the amount added is preferably 2 parts by weight or less based on the solid components forming the porous layer 20.
[0066] Methods for forming the porous layer 20 using a coating liquid containing a metal oxide precursor or metal oxide particles include spin coating, spraying, blade coating, roll coating, slit coating, printing, dip coating, etc. When manufacturing a member having a three-dimensional complex shape such as a concave surface, the spin coating or spraying method is preferable from the viewpoint of uniformity of the film thickness.
[0067] The first region 21, the second region 22, and the third region 23 can be formed by applying a coating liquid containing the first particles 24 to form a coating film, and then applying a coating liquid containing the second particles 25 before the surface of the coating film dries. The time from applying the coating liquid containing the first particles 24 to form a coating film to applying the coating liquid containing the second particles 25 depends on the type and temperature of the solvent, the thickness of the second region, etc., but is preferably within 2 minutes, and more preferably within 1 minute.
[0068] The thickness and porosity of the first region 21 and the third region 23 can be controlled by controlling the content of individual components, viscosity, and coating conditions of the coating liquid forming each region. The thickness and porosity of the second region 22 can be controlled by the drying conditions after application of the coating liquid containing the first particles 24. For example, if the drying time is short, the second region 22 will be thicker, and if the drying time is long, the second region 22 will be thinner.
[0069] In addition, a step of applying a coating liquid containing the first particles and the second particles may be added between the application of the coating liquid for forming the first region 21 and the application of the coating liquid for forming the third region 23 to form the second region 22. The coating liquid containing the first particles and the second particles and the coating liquid for forming the third region 23 are applied before the surface of the film made of the previously applied coating liquid dries. In this case, the thickness of the second region can be adjusted by the thickness of the coating film of the coating liquid containing the first particles 24 and the second particles 25.
[0070] After the coating liquid containing the first particles 24 and the coating liquid containing the second particles 25 are applied onto the substrate 10, drying and / or curing are performed. The drying and curing are performed to remove the solvent and to promote the reaction of the binder itself or the reaction between the binder and the particles. From the viewpoint of suppressing the influence of the residual solvent and the occurrence of cracks in the layer, the drying and / or curing temperature is preferably 15°C or higher and 200°C or lower, and more preferably 60°C or higher and 150°C or lower. The drying and / or curing time is preferably 5 minutes or higher and 24 hours or lower, and more preferably 15 minutes or higher and 5 hours or lower.
[0071] As described above, it is preferable that silicon oxide particles are dispersed in the coating liquid used to form the porous layer 20, because it is easy to manufacture and has relatively high stability. Hereinafter, a detailed description will be given of a case where the porous layer 20 is formed using a liquid in which silicon oxide particles are dispersed as the coating liquid for forming the porous layer 20. Hereinafter, both the coating liquid containing the first particles 24 and the coating liquid containing the second particles 25 will be described.
[0072] The coating liquid used to form the porous layer 20 can be prepared by mixing a liquid in which silicon oxide particles are dispersed, a binder solution containing a binder component, a solvent, and the like.
[0073] The liquid in which silicon oxide particles are dispersed can be prepared by adding water or a solvent to a dispersion of spherical or chain-shaped silicon oxide particles prepared by a wet method such as hydrothermal synthesis to dilute it. Alternatively, it can be prepared by a method of replacing the solvent of a dispersion of silicon oxide particles prepared by a similar wet method with a desired solvent by distillation or ultrafiltration, or a method of dispersing silicon oxide particles synthesized by a dry method such as fumed silica in water or a solvent by ultrasonic waves or a bead mill. When chain-shaped silicon oxide particles are used, particles of shapes such as perfect circles, ellipses, disks, rods, needles, and squares may be appropriately mixed in addition to chain-shaped particles. The ratio of particles of shapes other than chain-shaped particles that can be mixed with the whole particles can be appropriately determined taking into account the refractive index of the substrate and the film to be laminated.
[0074] The binder added to bind silicon oxide particles together is preferably a silicon oxide compound. A suitable example of the silicon oxide compound is a silicon oxide oligomer obtained by hydrolysis and condensation of a silicate ester.
[0075] The amount of the silicon oxide compound added in the coating liquid is preferably from 1 to 30% by mass, more preferably from 4 to 20% by mass, based on the silicon oxide particles, from the viewpoints of scratch resistance and anti-fogging properties.
[0076] There are several methods for adding silicon oxide oligomers to the dispersion of silicon oxide particles, including, for example, mixing a silicon oxide oligomer solution prepared in advance in water or a solvent with the dispersion of silicon oxide particles, and mixing a raw material for the silicon oxide oligomer with the dispersion of silicon oxide particles and then converting it into the silicon oxide oligomer.
[0077] Silicon oxide oligomers can be prepared by hydrolysis and condensation of silicate esters such as methyl silicate and ethyl silicate in a solvent or dispersion by adding water, acid, or base. Examples of acids that can be added to the silicate ester include hydrochloric acid, nitric acid, methanesulfonic acid, trifluoroacetic acid, trifluoromethanesulfonic acid, phosphoric acid, and p-toluenesulfonic acid. The base can be selected from ammonia and various amines, taking into consideration the solubility in the solvent and the reactivity of the silicate ester. When preparing the binder solution, it is also possible to heat the solution at a temperature of 80°C or less.
[0078] The weight-average molecular weight of the silicon oxide condensate contained in the binder solution is preferably 500 or more and 3000 or less in polystyrene equivalent. If the weight-average molecular weight is less than 500, cracks are likely to occur after curing, and the stability as a coating liquid is reduced. If the weight-average molecular weight exceeds 3000, the viscosity increases, and the voids inside the binder tend to become non-uniform, so that large voids are likely to occur.
[0079] When silicon oxide particles are chemically bonded to each other, a method of bonding silicon oxide particles to each other via highly activated silanol groups can be used. Specifically, a method of treating the surfaces of silicon oxide particles with a strong acid or a method of attaching silanol groups to the surfaces of silicon oxide particles can be used.
[0080] The solvent that can be used for the dispersion liquid of silicon oxide particles may be any solvent in which the raw material is uniformly dissolved and the reactant does not precipitate. The above-mentioned monohydric alcohols, dihydric or higher alcohols, ether alcohols, ethers, esters, ketones, aprotic polar solvents, etc. can be used. In addition, various aliphatic or alicyclic hydrocarbons such as n-hexane, n-octane, cyclohexane, cyclopentane, and cyclooctane, various aromatic hydrocarbons such as toluene, xylene, and ethylbenzene, or various chlorinated hydrocarbons such as chloroform, methylene chloride, carbon tetrachloride, and tetrachloroethane can also be used. In addition, two or more solvents selected from these can be mixed and used.
[0081] [Second embodiment] Depending on the application, such as when a member having the front-surface antireflection layer 30 is incorporated into a device, the metal oxide film of the front-surface antireflection layer 30 may be exposed to the atmosphere, and siloxane-based organic matter may adhere to the surface of the layer, increasing the contact angle of water. If the contact angle of water on the surface of the front-surface antireflection layer 30 becomes high and there is moisture on the surface that exceeds the amount of moisture that the member can retain, water droplets will form on the surface of the member, causing fogging.
[0082] Therefore, in this embodiment, as shown in FIG. 5, a hydrophilic polymer layer 50 is provided on the surface of the member that comes into contact with air (the surface of the antireflection layer 40) to suppress an increase in the contact angle of the member surface with water.
[0083] (hydrophilic polymer layer) The hydrophilic polymer layer 50 can be made of any compound containing a hydrophilic functional group, but a polymer having a hydrophilic group of an amphoteric ion is particularly preferred. The presence of the hydrophilic group of an amphoteric ion increases the hydrophilicity of the surface and reduces the electrical resistance, making it difficult for contaminants to adhere to the surface. As a result, it is possible to maintain high hydrophilicity for a long period of time. The presence of the hydrophilic polymer layer on the surface of the optical element prevents water that cannot be retained by the optical element from forming a water film on the surface of the optical element instead of water droplets, thereby suppressing the occurrence of fogging.
[0084] As the amphoteric ionic hydrophilic group, any one selected from the group consisting of sulfobetaine group, carbobetaine group, phosphorcholine group, sulfone group, phosphonate group, and carboxylic acid anhydride can be suitably used. The organic skeleton of the polymer having the amphoteric ionic hydrophilic group is not particularly limited.
[0085] In order to enhance the adhesion between the hydrophilic polymer layer 50 and the front-surface antireflection layer 30, it is preferable to select the chemical composition of the front-surface antireflection layer 30 in contact with the hydrophilic polymer layer 50. For example, in order to react with the silanol group of the silane coupling agent contained in the solution for forming the hydrophilic polymer layer 50, it is preferable to use silicon oxide on the surface of the front-surface antireflection layer 30 on which the hydrophilic layer is to be formed.
[0086] In general, in order to improve the anti-reflection performance of the multilayer film, it is preferable to lower the refractive index of the layer in contact with air. However, the compounds used to form the hydrophilic polymer layer 50 are generally silane coupling agents or hydrophilic polymers, and many of them have a refractive index of more than 1.4. Therefore, in order to maintain hydrophilicity by suppressing the adhesion of siloxane-based organic matter to the surface without affecting the anti-reflection performance of the front-surface anti-reflection layer 30, it is preferable to set the layer thickness of the hydrophilic polymer layer 50 to 1 nm or more and 20 nm or less.
[0087] If the hydrophilic polymer layer has such a thickness, it is possible to achieve high antireflection performance even when a hydrophilic layer is formed by designing the refractive index and film thickness of each layer of the antireflection layer.
[0088] The thickness of the hydrophilic polymer layer can be measured by the following method using an X-ray photoelectron spectrometer. The surface of the member is irradiated with an X-ray beam, and the concentration of the element derived from the hydrophilic polymer is measured from the intensity of the detected photoelectron peak. The element derived from the hydrophilic polymer can be measured, for example, by using sulfur if the hydrophilic group of the hydrophilic polymer is a sulfobetaine group, phosphorus if the hydrophilic group is a phosphorocholine group, or nitrogen if the hydrophilic group is a carbobetaine group. Next, after etching an arbitrary predetermined area of the surface of the member with an ion beam for a certain period of time, an X-ray beam is irradiated into the etched area to measure the concentration of the element derived from the hydrophilic polymer. The set of measuring the concentration of the element derived from the hydrophilic polymer and etching is repeated multiple times, and the depth D of the groove from the surface is physically measured. From the number of etchings and the depth D of the groove, the layer thickness of the hydrophilic polymer layer 50 etched in one etching process can be calculated.
[0089] Under the etching conditions calculated for the layer thickness etched in one etching step, etching and measurement of the concentration of the element derived from the hydrophilic polymer are repeated for the hydrophilic polymer layer 50 formed on the surface of the optical element until the element derived from the hydrophilic polymer becomes undetectable. In the present invention, the thickness of the hydrophilic polymer layer 50 is determined as the value obtained by multiplying the number of etchings at the point when the detection intensity of the element derived from the hydrophilic polymer disappears by the layer thickness etched in one etching step.
[0090] The hydrophilic polymer layer 50 can be formed by supplying a solution containing a compound having a hydrophilic functional group onto the antireflection layer by a method such as spin coating, blade coating, roll coating, slit coating, printing, or dip coating, and curing the solution.
[0091] The compound containing a functional group having hydrophilicity is particularly preferably a polymer having a hydrophilic group of an amphoteric ion. Preferred main chain structures of the hydrophilic polymer include acrylic resins, methacrylic resins, polyurethane resins, polyimide resins, polyamide resins, epoxy resins, polystyrene resins, polyester resins, and the like.
[0092] As the solvent for the hydrophilic polymer solution, it is preferable to select a solvent having high compatibility with the hydrophilic polymer to be used from among alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, ethylene glycol, and propylene glycol; ketones such as acetone and methyl ethyl ketone; ethers such as diethyl ether and tetrahydrofuran; aromatic hydrocarbon compounds such as benzene, toluene, and xylene; aliphatic hydrocarbon compounds such as n-hexane; alicyclic hydrocarbon compounds such as cyclohexane; and acetates such as methyl acetate and ethyl acetate.
[0093] [Third embodiment] FIG. 6 shows an example of a preferred embodiment of an imaging device according to the present invention, and illustrates the configuration of a single-lens reflex digital camera to which a lens barrel (interchangeable lens) which is an example of the optical device of the present invention is coupled.
[0094] The optical instrument of the present invention refers to instruments equipped with an optical system including the member of the present invention, which has a porous layer formed on a transparent substrate, such as binoculars, microscopes, semiconductor exposure devices, and interchangeable lenses, or instruments that generate images using light that has passed through the member of the present invention.
[0095] The imaging device of the present invention refers to a camera system such as a digital still camera or a digital video camera, or an electronic device equipped with an imaging element that receives light that has passed through the member of the present invention, such as a mobile phone. Note that a modular form mounted on an electronic device, such as a camera module, may also be considered as an imaging device.
[0096] In FIG. 6, a camera body 320 and a lens barrel 310, which is an optical device, are coupled together, and the lens barrel 310 is a so-called interchangeable lens that is detachable from the camera body 320.
[0097] Light from a subject passes through an optical system consisting of multiple lenses 312, 313, etc. arranged on the optical axis of the photographing optical system inside housing 311 of lens barrel 310, and is received by the image sensor. The member according to the present invention is preferably used for, for example, lens 312 inside the housing, which is the lens most likely to become cloudy, but may be used for any of the lenses that make up the optical system.
[0098] Here, the lens 313 is supported by an inner tube 314 and is supported movably relative to the outer tube of the lens barrel 311 for focusing and zooming.
[0099] During an observation period before shooting, light from a subject is reflected by a main mirror 322 in a housing 321 of the camera body, passes through a prism 323, and then a shot image is projected to the photographer through a viewfinder lens 324. The main mirror 322 is, for example, a half mirror, and the light that passes through the main mirror is reflected by a sub-mirror 325 in the direction of an AF (autofocus) unit 326, and this reflected light is used, for example, for distance measurement. The main mirror 322 is attached and supported by a main mirror holder 327, for example, by adhesive. During shooting, the main mirror 322 and the sub-mirror 325 are moved out of the optical path via a driving mechanism (not shown), a shutter 328 is opened, and a shooting light image incident from the lens barrel 310 is formed on an image sensor 329. The aperture 315 is configured so that the brightness and focal depth during shooting can be changed by changing the opening area.
[0100] As shown in FIG. 6, by using the member according to the present invention, it is possible to prevent the occurrence of fogging in the optical system due to changes in the external environment, and to obtain a clear image. EXAMPLES
[0101] Examples and comparative examples according to the present invention will be described below. However, the present invention is not limited to the following examples as long as the gist of the present invention is not exceeded.
[0102] (1) Preparation of Silicon Oxide Particle Dispersion 1 for Forming the First Region of the Porous Layer 1-Ethoxy-2-propanol was added to 370 g of a 1-methoxy-2-propanol (PGME) dispersion of spherical silicon oxide particles (PGM-ST, manufactured by Nissan Chemical Industries, Ltd., average particle size 12 nm, solid content concentration 30 mass%) to prepare 2018.2 g of a 1-ethoxy-2-propanol dispersion of spherical silicon oxide particles with a solid content concentration of 5.5 mass%.
[0103] In a separate container, 54 g of 0.01 mol / l dilute hydrochloric acid was slowly added to a solution of 62.6 g of ethyl silicate and 36.8 g of 1-ethoxy-2-propanol, and the mixture was stirred at room temperature for 90 minutes, and then heated at 40°C for 1 hour to prepare a silicon oxide oligomer solution with a solids concentration of 11.8 mass%.
[0104] To the resulting 1-ethoxy-2-propanol dispersion of spherical silicon oxide particles, 94.1 g of the silicon oxide binder solution was slowly added, and the mixture was stirred at room temperature for 2 hours to prepare silicon oxide particle coating solution 1.
[0105] The particle size distribution of the coating liquid was measured by dynamic light scattering (Zetasizer Nano ZS, manufactured by Malvern Instruments) to confirm that spherical silicon oxide particles with an average particle size of 15 nm were dispersed.
[0106] (2) Preparation of Silicon Oxide Particle Dispersion 2 for Forming the Third Region of the Porous Layer 1-propoxy-2-propanol was added to 500 g of a 2-propanol (IPA) dispersion of chain-like silicon oxide particles (IPA-ST-UP manufactured by Nissan Chemical Industries, Ltd., average particle size 12 nm, solid content concentration 15 mass%) while distilling off the IPA, to prepare 433.3 g of a 1-propoxy-2-propanol dispersion of chain-like silicon oxide particles with a solid content concentration of 17.3 mass%. In a separate container, 54 g of 0.01 mol / l dilute hydrochloric acid was slowly added to a solution of 62.6 g of ethyl silicate and 36.8 g of 1-propoxy-2-propanol, and the mixture was stirred at room temperature for 90 minutes.Then, the mixture was heated at 40°C for 1 hour to prepare a silicon oxide oligomer solution with a solid content of 11.8% by mass.
[0107] 25.4 g of the silicon oxide oligomer solution was slowly added to the 1-propoxy-2-propanol dispersion of the chain silicon oxide particles, and the mixture was stirred at room temperature for 2 hours to prepare silicon oxide particle coating solution 2.
[0108] Particle size distribution measurement of the coating liquid by dynamic light scattering (Zetasizer Nano ZS, manufactured by Malvern Instruments) confirmed that chain-like silicon oxide particles with a minor axis of 11 nm and a major axis of 77 nm were dispersed.
[0109] (3) Measurement of film thickness and pores After coating the anti-reflection layer formed on the substrate with a carbon film and a Pt-Pd film, the sample was sliced in an electron beam processing device (FIB-SEM; FEI Nova600) and observed with a scanning transmission electron microscope (STEM; Hitachi S-5500). The thickness of each layer was measured from the obtained secondary electron image. The presence or absence of the second region can be determined by binarizing the obtained secondary electron image and calculating the change in porosity by calculating the area of the part occupied by voids from the substrate side to the surface side.
[0110] (4) Refractive index measurement The change in the polarization state of incident light and reflected light was measured using a spectroscopic ellipsometer in the wavelength range from 380 nm to 800 nm, and the refractive index was calculated. d The refractive index was calculated using the film thickness measured in (3).
[0111] (5) Anti-fogging evaluation Using an anti-fogging property evaluation device (AFA-2 manufactured by Kyowa Interface Science Co., Ltd.), the transparent substrate kept at 25°C was left in an atmosphere of 25°C and 70% RH while being cooled to 15°C, and the transmission image was recorded every second for up to 300 seconds. A compression anti-fogging index analysis was performed from the transmission image, and the time change of the compression anti-fogging index was plotted.
[0112] From the obtained plot, the time until the compression anti-fogging index started to decrease from the initial value was read, and the anti-fogging property was evaluated according to the following criteria. The longer the time until the compression anti-fogging index started to decrease from the initial value, the better the anti-fogging property. d =1.52) will start to cloud over in 68 seconds.
[0113] (6) Reflectance evaluation The absolute reflectance was measured from 380 nm to 780 nm using a reflectance measuring device (USPM-RU manufactured by Olympus Corporation), and the average reflectance from 400 to 700 nm was calculated (average reflectance). Evaluation was performed according to the following criteria: The smaller the average reflectance before and after water absorption, the better the reflective performance.
[0114] Example 1 A 40 mm square, 3 mm thick flat glass plate (S-BSL7, manufactured by Ohara Corporation) d =1.52), an appropriate amount of silicon oxide particle dispersion liquid 1 was dropped onto the substrate, and the substrate was spin-coated at 4000 rpm for 12 seconds to form a coating film. Then, before the coating film made of silicon oxide particle dispersion liquid 1 dried, an appropriate amount of silicon oxide particle dispersion liquid 2 was subsequently dropped onto the substrate, and the substrate was spin-coated at 1500 rpm for 30 seconds to form a coating film. After that, the substrate was heated at 140°C for 30 minutes in a hot air circulating oven to harden the coating film, thereby producing a member having a porous layer.
[0115] Example 2 A member having a porous layer was obtained in the same manner as in Example 1, except that an appropriate amount of silicon oxide particle dispersion liquid 1 was dropped and spin-coated at 4000 rpm for 16 seconds.
[0116] Example 3 A member having a porous layer was produced in the same manner as in Example 1, except that a coating liquid for forming a porous layer was applied in the following procedure.
[0117] An appropriate amount of silicon oxide particle dispersion liquid 1 was dropped and spin-coated at 5000 rpm for 20 seconds. Next, an appropriate amount of a liquid in which silicon oxide particle dispersion liquid 1 and silicon oxide particle dispersion liquid 2 were mixed at a ratio of 10:1 was dropped and spin-coated at 5000 rpm for 10 seconds, and an appropriate amount of silicon oxide particle dispersion liquid 2 was dropped and spin-coated at 1500 rpm for 30 seconds.
[0118] Example 4 After forming the porous layer, a surface antireflection layer consisting of a combination of a layer containing silicon oxide, a layer containing titanium oxide, and a layer containing magnesium fluoride was formed based on a design taking antireflection performance into consideration, and a porous layer was then formed in the same manner as in Example 1 to obtain a member.
[0119] When forming the front-surface antireflection layer, the temperature of the substrate, the ultimate vacuum pressure, and the pressure during film formation of each layer were adjusted so as to obtain the desired refractive index. In addition, silicon oxide pellets (SiO2E type manufactured by Canon Optron Inc.), pellets containing titanium oxide (manufactured by Nichia Corporation), and magnesium fluoride pellets (MgF2 manufactured by Rare Metals Co., Ltd.) were used to form each layer. The refractive index and film thickness of each layer of the front-surface antireflection layer are shown in Table 1. [Table 1]
[0120] Comparative Example 1 A 40 mm square, 3 mm thick flat glass plate (S-BSL7, manufactured by Ohara Corporation) d On the substrate (fiber-reinforced plastic film (fiber-reinforced plastic film) ... = 1.52), magnesium fluoride was deposited as a base film by vapor deposition, and then an appropriate amount of silicon oxide particle dispersion liquid 2 was dropped and spin-coated at 1500 rpm for 30 seconds. The substrate was then heated at 140°C for 30 minutes in a hot air circulating oven and cured to produce a member having a porous layer. The magnesium fluoride base film is a layer provided to reduce the difference in refractive index between the substrate and the porous layer and reduce reflection.
[0121] Comparative Example 2 Except for forming the porous layer and then the front-surface antireflection film, a member having a porous layer was produced in the same manner as in Comparative Example 1. The front-surface antireflection film was a multilayer vapor deposition film shown in Table 1, as in Example 4.
[0122] (Evaluation of Examples 1 to 3 and Comparative Examples 1 to 2) The configurations and evaluation results of the members produced in Examples 1 to 4 are summarized in Table 2, and the configurations and evaluation results of the members produced in Comparative Examples 1 and 2 are summarized in Table 3. [Table 2] [Table 3]
[0123] In the anti-fogging evaluation, the members produced in Comparative Examples 1 and 2 became fogged in 102 [sec], whereas the members produced in Examples 1 to 4 did not fog up in less than 110 [sec], confirming their excellent anti-fogging properties. The glass substrate was found to have anti-fogging properties, as it became fogged up in 68 seconds in the anti-fogging evaluation.
[0124] From the results of Examples 1 to 3 and Comparative Example 1, it can be seen that the configuration of Comparative Example 1, in which a base layer is provided for anti-reflection, has a higher average reflectance due to water absorption than the configurations of Examples 1 to 3 according to the present invention. The reflection characteristics measured before and after water absorption for each of the members of Example 1 and Comparative Example 1 are shown in Figures 7 and 8. The average reflectance difference before and after water absorption for Example 1 was 1.53%, and the average reflectance difference before and after water absorption for Comparative Example 1 was 1.65%, meaning that Example 1 had superior anti-reflection properties.
[0125] In both of the members of Example 4 and Comparative Example 2, a surface antireflection layer was formed on the porous layer. It was confirmed that the antireflection properties were enhanced by combining both with an antireflection layer. However, although the average reflectance before water absorption was equivalent in Example 4 and Comparative Example 2, a large difference in the average refractive index occurred after water absorption, and it was confirmed that Example 4 had superior antireflection properties. The average reflectance difference before and after water absorption in Example 4 was 0.73%, and the average reflectance difference before and after water absorption in Comparative Example 2 was 1.03%.
[0126] From the above results, it was confirmed that the member according to the present invention has excellent anti-fogging and anti-reflection properties before and after moisture absorption. [Industrial Applicability]
[0127] The members of the present invention can be used for general purposes such as window glass, mirrors, lenses, transparent shields, transparent films, etc. They can also be used as optical components such as optical lenses, optical mirrors, optical filters, eyepieces, and flat covers and dome covers for outdoor cameras and surveillance cameras in imaging and projection systems. [Explanation of symbols]
[0128] 100 parts 10 Base material 20 Porous layer 21 The First Area 22 The Second Region 23 The Third Region 24 First Particle 25 Second Particle 30 Surface antireflection layer 40 Base anti-reflective layer 50 Hydrophilic polymer layer 310 Lens barrel 320 Camera body 312, 313 Lenses 328 Shutter 329 Image sensor
Claims
1. An optical member comprising a porous layer on a substrate, the porous layer has, in this order from the substrate side, a first region, a second region, and a third region; the first region includes first particles, the third region includes second particles having a shape different from that of the first particles, and the second region includes the first particles and the second particles, the average porosity of the second region is greater than the average porosity of the first region; An optical member, wherein the average porosity of the third region is greater than the average porosity of the second region.
2. 2. The optical member according to claim 1, wherein the porosity of the first region is 10% or more and 30% or less, and the porosity of the third region is 40% or more and 60% or less.
3. 3. The optical member according to claim 1, wherein the third region has a thickness of 0.2 μm or more and 2 μm or less.
4. 4. The optical member according to claim 1, wherein the first region has a thickness of 50 nm or more and 150 nm or less.
5. 5. The optical member according to claim 1, wherein the average pore size of the pores contained in the porous layer is 3 nm or more and 50 nm or less.
6. The pore volume of the pores contained in the porous layer is 0.1 cm 3 / g or more 1.0cm 3 6. The optical member according to claim 1, wherein the viscosity is 0.1 to 1000 MPa.
7. 7. The optical member according to claim 1, wherein the first particles are spherical silicon oxide particles, and the second particles are chain-like silicon oxide particles.
8. 8. The optical member according to claim 7, wherein the spherical silicon oxide particles have an average particle size of 5 nm or more and 100 nm or less, and the chain-like silicon oxide particles have an average minor axis of 5 nm or more and 40 nm or less.
9. 9. The optical member according to claim 1, further comprising a laminate of a plurality of layers having mutually different refractive indices on a surface of the porous layer and / or between the porous layer and the substrate.
10. 10. The optical member according to claim 9, wherein the laminate comprises at least two layers selected from a low refractive index layer having a refractive index of less than 1.4, a medium refractive index layer having a refractive index of 1.4 or more and less than 1.8, and a high refractive index layer having a refractive index of 1.8 or more.
11. 11. The optical member according to claim 1, further comprising a hydrophilic polymer layer on a surface of the optical member that is in contact with air.
12. 12. The optical member according to claim 11, wherein the hydrophilic polymer layer is a polymer having a zwitterionic hydrophilic group.
13. 13. The optical member according to claim 12, wherein the hydrophilic group of the zwitterion is any one selected from the group consisting of a sulfobetaine group, a carbobetaine group, a phosphorcholine group, a sulfone group, a phosphonate group, and a carboxylic acid anhydride group.
14. 14. The optical member according to claim 11, wherein the hydrophilic polymer layer has a thickness of 1 nm or more and 20 nm or less.
15. An optical device comprising a housing and an optical system made up of a plurality of lenses within the housing, An optical device, wherein at least one of the lenses is the optical member according to claim 1 .
16. An imaging device comprising: a housing; an optical system including a plurality of lenses disposed within the housing; and an imaging element that receives light that has passed through the optical system, An imaging device, wherein at least one of the lenses is an optical member according to claim 1 .
17. A method for producing the optical member according to any one of claims 1 to 14, comprising the steps of: A step of supplying a first coating liquid containing first particles onto the substrate to form a first coating film; supplying a second coating liquid containing second particles having a shape different from that of the first particles onto a substrate to form a second coating film; Including, A method for producing an optical member, comprising forming the second coating film after the first coating film is formed and before the first coating film is dried.
18. 18. The method for producing an optical member according to claim 17, wherein the first coating liquid contains spherical silicon oxide particles, and the second coating liquid contains chain-like silicon oxide particles.
19. 19. The method for producing an optical member according to claim 17, wherein the first coating liquid and the second coating liquid each contain a binder component.
20. 20. The method for producing an optical member according to claim 19, further comprising the step of forming a laminate of a plurality of layers having mutually different refractive indices by a vapor deposition method between the substrate and the porous layer.
21. 21. The method for producing an optical member according to claim 17, further comprising the step of forming a laminate of a plurality of layers having mutually different refractive indices on a surface of the porous layer by a vapor deposition method.
22. 22. The method for manufacturing an optical member according to claim 17, further comprising a step of supplying a solution containing a compound having a hydrophilic functional group to a surface of the optical member in contact with air to form a hydrophilic polymer layer.
23. 23. The method for producing an optical member according to claim 22, wherein the hydrophilic functional group is any one selected from the group consisting of a sulfobetaine group, a carbobetaine group, a phosphorcholine group, a sulfone group, a phosphonate group, and a carboxylic acid anhydride.
Citation Information
Patent Citations
Production of functionally gradient material
JP1994025775A
Optical component having antifogging film and semiconductor device
JP2013105846A